Augmented unipolar lead based formula for calculation of meanelectrical axis of the heart - H, MOHAN N; TAMULI, M K; DAS, ANUBRATA (The Indian Journal of Animal Sciences, 2011)
The present study was conducted to derive a mathematical formula for the calculation of MEA from net voltages of QRS complexes in the all the augmented unipolar extremity leads- aVF, aVL and aVR. θ the angle subtended by the lead I of the electrocardiogram of the MEA was equal to Arctan √3(aVF)/(aVL-aVR). The MEA values calculated using the proposed formula was compared with MEA angles determined using different formulae as well as by dropping perpendiculars in the Einthoven’s triangle. With the formula proposed, comparable results were obtained with methods, which accounted for the comparative lead strength of augmented unipolar and bipolar leads of the ECG. The MEA values calculated using various methods different nonsignificantly. MEA obtained from the augmented leads after applying correction does not differ significantly from the values without correction and for all practical purposes; any of methods may be used for computation of MEA. However, since the ECG machines can act as source of error, that various methods for calculation of MEA must be analysed under large sample size before being put into use in ECG machines.